Problem-based learning (PBL) library resources and support: survey insights from first-year dental students. - Silverman, Jennifer A. (Medical Reference Services Quarterly)
Problem-based learning (PBL) is part of an integrated dental school curriculum using patient cases to learn about biomedical sciences. In PBL, students must find and evaluate information sources to support their patient cases. The library supports PBL students through course-related LibGuides, recommended textbooks, and librarian assistance. A feedback survey was conducted with first-year dental students to assess their perceptions of the usefulness of PBL library resources and the benefits of librarian support. Results indicate that students found PBL resources useful and few asked for librarian assistance. Analyzing this data led to changes in library instruction.